Fundamentals of Federal Taxation – Federal Estate Tax (Book). - Cannon, Arthur M.; Roller, Julius (The Accounting Review, 1952)
Reviews the book "Fundamentals of Federal Taxation–Federal Estate Tax," by Adrian W. DeWind and Herrick K. Lidstone.